The effect of chronic ingestion of afriplex grt™ on myocardial insulin resistance and mitochondrial function – a preclinical study. - Kroukamp, Marlouw (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScMedSc)--Stellenbosch University, 2018.